A cautionary tale of sense-antisense gene pairs: independent regulation despite inverse correlation of expression - Goyal, Ashish; Fiškin, Evgenij Ilʹič; Gutschner, Tony; Polycarpou-Schwarz, Maria; Groß, Matthias; Neugebauer, Julia; Gandhi, Minakshi; Caudron-Herger, Maïwen; Benes, Vladimir; Diederichs, Sven (Nucleic acids research, 2017)
Long non-coding RNAs (lncRNAs) have been proven to play important roles in diverse cellular processes including the DNA damage response. Nearly 40% of annotated lncRNAs are transcribed in antisense direction to other genes and have often been implicated in their regulation via transcript- or transcription-dependent mechanisms. However, it remains unclear whether inverse correlation of gene expression would generally point toward a regulatory interaction between the genes. Here, we profiled lncRNA and mRNA expression in lung and liver cancer cells after exposure to DNA damage. Our analysis revealed two pairs of mRNA-lncRNA sense-antisense transcripts being inversely expressed upon DNA damage. The lncRNA NOP14-AS1 was strongly upregulated upon DNA damage, while the mRNA for NOP14 was downregulated, both in a p53-dependent manner. For another pair, the lncRNA LIPE-AS1 was downregulated, while its antisense mRNA CEACAM1 was upregulated. To test whether as expected the antisense genes would regulate each other resulting in this highly significant inverse correlation, we employed antisense oligonucleotides and RNAi to study transcript-dependent effects as well as dCas9-based transcriptional modulation by CRISPRi/CRISPRa for transcription-dependent effects. Surprisingly, despite the strong stimulus-dependent inverse correlation, our data indicate that neither transcript- nor transcription-dependent mechanisms explain the inverse regulation of NOP14-AS1:NOP14 or LIPE-AS1:CEACAM1 expression. Hence, sense-antisense pairs whose expression is strongly—positively or negatively—correlated can be nonetheless regulated independently. This highlights the requirement of individual experimental studies for each antisense pair and prohibits drawing conclusions on regulatory mechanisms from expression correlations.